The ameliorative effect of ascorbic acid on the oxidative status, live weight and recovery rate in road transport stressed goats in a hot humid tropical environment - Nwunuji, Tanko Polycarp; Mayowa, Opeyemi Onilude; Mohd Yusoff, Sabri; Bejo, Siti Khairani; Salisi, Shahrom; Abd Wahid, Mohd Effendy (Japanese Society of Animal Science, 2014)
The ameliorative effect of ascorbic acid (AA) on live weight following transportation is vital in animal husbandry. This study investigated the influence of AA on live weight, rectal temperature (rt), and oxidative status of transport stressed goats in a hot humid tropical environment. Twenty-four goats were divided into four groups, A, B, C and D of six animals each. Group A were administered AA 100 mg/kg intramuscularly 30 min prior to 3.5 h transportation. Group B was administered AA following transportation. Group C were transported but not administered AA as positive controls while group D were not transported but were administered normal saline as negative controls. Live weight, rt and blood samples were collected before, immediately post-transport (pt), 24 h, 3 days, 7 days and 10 days pt. Plasma was used for malondialdehyde (MDA) analysis while hemolysates were used for superoxide dismutase (SOD) analysis. There was minimal live weight loss in group A compared to groups B and C. Group A recorded reduced MDA activities and increased SOD activities compared to groups B and C which recorded significantly high MDA activities. This study revealed that AA administration ameliorated the stress responses induced by transportation in animals in hot humid tropical environments. The administration of AA to goats prior to transportation could ameliorate stress and enhance productivity.